Mathematical models for temperature distribution in oil wells - B. Ajaj, Wisam; Amhmad Borhana Omran, Abdoulhdi; M. Elfaghi, Abdulhafid (School of Engineering, Taylor’s University, 2022)
The oil temperature at the surface of the oil well is low compared to the oil temperature at the reservoir. The drop of temperature is due to heat transfer to the tubing wall. The temperature distribution of the oil from the reservoir to the surface and surrounding layers is studied in this paper. Two mathematical models for production and shut-in cases are developed to study the parameters affecting the temperature profile in oil wells. The natural flow of oil wells in Alwahat area located 70 Kilometres south of Marada area east of Libya in the Zaggut field called (6Q1-59) is taken as a study case. In production case, different mass flow rates in winter and summer seasons are studied. The temperature profile in the horizontal direction is estimated at different depths. In shut-in case, steady-state energy balance equation is solved using finite difference method, the results are compared with the actual date taken from the Waha company reports.